2008
DOI: 10.1088/0022-3727/41/6/065207
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of an Ar/Cl2inductively coupled plasma: study of the effect of bias, power and pressure and comparison with experiments

Abstract: A hybrid model, called the hybrid plasma equipment model, was used to study Ar/Cl2 inductively coupled plasmas used for the etching of Si. The effects of substrate bias, source power and gas pressure on the plasma characteristics and on the fluxes and energies of plasma species bombarding the substrate were observed. A comparison with experimentally measured etch rates was made to investigate how the etch process is influenced and which plasma species mainly account for the etch process. First, the general pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 31 publications
3
44
0
Order By: Relevance
“…Since their fluxes are a few orders of magnitude higher than the ion flux, it can be concluded that the surface is effectively converted to physisorbed SiF 4 molecules, which are very easily sputtered even by low energy ions. These observations are in line with basic ion-enhanced etching principles where a combination of chemical etching and ion sputtering yields a much higher etch rate than each process separately 36. Although direct sputtering of SiF 0-3 surfaces might thus not occur often in reality, as the surface is usually converted to SiF 4 during etching, figures 2 and 3 still give us important information on the behavior of the ions on the surface, like sputtering and incorporation yields.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…Since their fluxes are a few orders of magnitude higher than the ion flux, it can be concluded that the surface is effectively converted to physisorbed SiF 4 molecules, which are very easily sputtered even by low energy ions. These observations are in line with basic ion-enhanced etching principles where a combination of chemical etching and ion sputtering yields a much higher etch rate than each process separately 36. Although direct sputtering of SiF 0-3 surfaces might thus not occur often in reality, as the surface is usually converted to SiF 4 during etching, figures 2 and 3 still give us important information on the behavior of the ions on the surface, like sputtering and incorporation yields.…”
supporting
confidence: 77%
“…For typical wafer processing plasmas, the flux of neutrals is usually 100 to 1000 times higher than the ion flux. 36 As a result, the surface is always heavily fluorinated before sputtering occurs. It can be noted from Indeed, because the layer of (physisorbed) SiF 4 molecules is easily removed by ion impact, the underlying SiF 0-3 layers can still be reached by ions.…”
Section: Sputter Yieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial increase was again attributed to the reaction-limited regime, whereas the decrease was attributed to lower ion energies due to the reduction in dc self-bias and ion-assisted desorption of reactive species at the substrate prior to the etch reactions. Despiau-Pujo et al 16 and Tinck et al 22 showed through simulation that ion fluxes increase with increase in ICP power. Ion flux (F ion ) in a collisionless sheath is given by the following relationship 16 :…”
Section: Effect Of Icp Power On the Etch Characteristicsmentioning
confidence: 99%
“…Neutral-neutral reactions [5] Ion-neutral reactions [5] CF4 discharge Electron collision reactions [2] Neutral-neutral reactions…”
mentioning
confidence: 99%